Hyperoxia and the antimicrobial susceptibility of Escherichia coli and Pseudomonas aeruginosa. - Muhvich, K H (1989)
We have tested the ability of hyperoxia (98% O2-2% CO2 at 2.8 atmospheres absolute [ca. 284.6 kPa]) to enhance killing of Escherichia coli (serotype O18 or ATCC 25922) by nitrofurantoin, sulfamethoxazole, trimethoprim, gentamicin, and tobramycin. We have also looked for interactions between hyperoxia and the aminoglycosides against Pseudomonas aeruginosa ATCC 27853. Hyperoxia significantly enhanced bacteriostatic activity of nitrofurantoin and trimethoprim as measured by MIC testing. The possibility exists that these effects might be due to the method required to tests MICs under hyperoxic conditions rather than to the effect of hyperoxia itself. In addition, hyperoxia enhanced killing of bacteria by trimethoprim as measured by MBC testing. Hyperoxia decreased numbers of E. coli by 1.3 log10 and P. aeruginosa by 2.7 log10 in cation-supplemented Mueller-Hinton broth medium. The bacteriostatic effects of hyperoxia did not affect MICs of gentamicin or tobramycin. The lack of interaction between hyperoxia and gentamicin or tobramycin was confirmed by determining the number of viable bacteria remaining after 24 h of exposure to hyperoxia by using a pour plate method. We conclude that hyperoxia potentiates the antimicrobial activity of the reduction-oxidation-cycling antibiotic tested (nitrofurantoin) and of one of the antimetabolites tested (trimethoprim). Hyperoxia does not enhance the bactericidal effects of gentamicin and tobramycin, which require oxidative metabolism for transport into bacterial cells.